2012
DOI: 10.1371/journal.pone.0040529
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors Influencing Hospitalized Patients with Pneumonia Due to Influenza A(H1N1)pdm09 in Mexico

Abstract: BackgroundIn addition to clinical aspects and pathogen characteristics, people's health-related behavior and socioeconomic conditions can affect the occurrence and severity of diseases including influenza A(H1N1)pdm09.Methodology and Principal FindingsA face-to-face interview survey was conducted in a hospital in Mexico City at the time of follow-up consultation for hospitalized patients with pneumonia due to influenza virus infection. In all, 302 subjects were enrolled and divided into two groups based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…A similar study in New York City, United States, demonstrated comparable results, suggesting that individuals in a lower socioeconomic status were more vulnerable to severe H1N1 illness 7 (#1542, Type IV). A more specific examination of disparities associated with the H1N1 pandemic indicated that disparities in exposure, susceptibility, and access to health care were clearly evident among racial and ethnic minorities in the United States 8 (#1553, Type V) and in Mexico 9 (#1578, Type V). This disproportionate burden is confirmed with COVID-19 10 (#189, Type IV).…”
Section: Resultsmentioning
confidence: 99%
“…A similar study in New York City, United States, demonstrated comparable results, suggesting that individuals in a lower socioeconomic status were more vulnerable to severe H1N1 illness 7 (#1542, Type IV). A more specific examination of disparities associated with the H1N1 pandemic indicated that disparities in exposure, susceptibility, and access to health care were clearly evident among racial and ethnic minorities in the United States 8 (#1553, Type V) and in Mexico 9 (#1578, Type V). This disproportionate burden is confirmed with COVID-19 10 (#189, Type IV).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Cambodia reported that patients with avian influenza H5N1 virus infection traveled up to 476 km prior to hospital admission [17]. Thus, along with socioeconomic conditions [18], the condition of patient transport could be a major risk factor related to disease severity and prognosis in low- and middle-income countries. Although we found no statistically significant differences between patients who were transferred from local hospitals and those who were not, Kaplan–Meier curves revealed that transferred patients tended to have shorter survival times than non-transferred patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that increasing knowledge about COVID-19 is important for the nursing care workers themselves, it is also useful for increasing knowledge and appropriate behaviors for preventing infection among older adults who are receiving care from the nursing care workers. In addition, at the time of the influenza H1N1pdm09 pandemic, a study in Mexico indicated that one of the risk factors of hospitalization was a lack of information regarding the importance of early access to health care [ 20 ]. The Mexican government has used taxi windows to distribute information and to encourage people to seek medical care early and to announce that there was a free medical care program.…”
Section: Discussionmentioning
confidence: 99%